Partially premixed combustion multi-cylinder engine cycle-to-cycle-oriented temperature estimation and control. (2017) - Yin, Lianhao; Ingesson, Gabriel; Johansson, Rolf; Tunestål, Per; Johansson, Bengt
Advanced combustion concepts like partially premixed combustion (PPC) are sensitive to inlet gas conditions especially inlet temperature. To estimate the combustion parameters like ignition delay on a cycle-to-cycle basis, both complementary filter and extended Kalman filter were designed to estimate the inlet temperature, and the ignition delay was calculated with properly estimated temperature. A two valve fast thermal management system was used to control the inlet temperature, and a PI controller with the lambda tuning method was used. The estimation and control algorithm were verified on a six-cylinder heavy duty engine.